ANALYSIS OF VALUE CHAIN CRISAN CUTTING INTEREST (Case Study of Chrysanthemum Cut Flower Farmer Group in Sidomulyo Village, Batu District, Batu City) - Winda Yanuaristy; Djoko Koestiono; Abdul Wahib Muhaimin (Agricultural Socio-Economics Journal, 2021)
This study aims to analyze the value chain of chrysanthemum cut flower farmers. The object of this research is located in Sidomulyo Village, Kec. Batu, Stone Town. This research was conducted on 34 respondents of chrysanthemum cut flower farmers using the census method. Data analysis using the Value Chain Analysis method by Kaplinsky and Morris. The results of this study indicate that the chrysanthemum cut flower farmer groups in the village of Sidomulyo have a value chain, namely, collectors (Florist) â†’ Event Organizer / Florist. Value Chain Mapping shows that all activities in the production of sudan chrysanthemum cut flowers are quite optimal, but there are 2 points that are lacking in outbound logistics and supporting activities in Product Segment Determination and Key Market Success Factors. Chrysanthemum cut flowers are influenced by price, constraints on delivery, packaging, flexibility and innovation